A stochastic simulation approach to estimating the economic impacts of climate change in Bangladesh - James Thurlow; Paul Dorosh; Winston Yu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Climate change assessments often inadequately address uncertainty when estimating damages. Using a dynamic economy-wide model of Bangladesh, we estimate and decompose damages from historical climate variability and future anthropogenic climate change. Our stochastic simulation approach avoids biases caused by non-linear damage functions and fixed occurrences of extreme events in historical data. Using ten climate projections, we find that future anthropogenic climate change damages until 2050 are, on average, one-fifth of those from historical climate variability. Climate change also alters the temporal distribution of damages and slows Bangladesh's long- run shift (adaptation) into dry (winter) season rice production.
Keywords: D58; Q54; Q56; 330; climate change; uncertainty; stochastic simulation; CGE model; agriculture; Bangladesh; Klimawandel; CGE-Modelling; Allgemeines Gleichgewicht; Landwirtschaft; Bangladesch